Philips Multinational Conglomerate Company / Mohd Amirul Hakimi Mat Nasir - Mat Nasir, Mohd Amirul Hakimi (2022)
PHILIPS company is a world-wide company covering more than hundreds of countries supplying their product over more than 10 decades. The company provides Personal Healthcare that focus the Personal Care, Consumer Electronics and Domestic Appliance, Connected Care and Diagnosis & Treatment that related to Medical Systems. This case study focuses on the product of Philips Universal Remote Control to analyse the weakness and come out with a good invention. This product found to be high chance for being broke by the use of usual material for any plastic product especially remote control. Besides, the slim size makes it much easier to break. Come out with solution, the company should manage to study the suitable material and also increase the size. the remote control also comes with no base with make it lost. This is a very common problem happen to every household dealing with remote control. With an innovation to the remote control by our company, the suitable base will create to overcome the problem that introduce some of features. The features work to increase the function of the remote control itself. Despite for having many buttons on the remote control, the new innovation will decrease the buttons and change it with voice detection system. These features will replace the function of buttons since to much button make user hard to understand the function with a bundle of manual that also sometimes not really helpful to use especially to elder user. A new product will create to increase the function and design of remote control widely be used by all user.